Global Managing Mastering the Spin of a Complex World - Ernst, Christopher (Center for Creative Leadership, 2002)
As the global economy has come of age, many managers have been thrust into leadership roles in which their skills don't match the requirements of the job. But are the capabilities needed to succeed in a global context really so different from those that are critical for domestic managers? And if there are differences, what can be done to develop these new skills?
Online resource; Title from title page (viewed January 1, 2002)
Keywords: Electronic books; local